Analysis of Musthafa Umar’s exegesis methodology in the Tafsir al-Ma’rifah - Saiin, Asrizal; M. Kafrawi,; Mohd Nazri Ahmad,; Mohd Faizulamri Mohd Saad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The objective of this study is to analyze the methodology of Musthafa Umar on preaching using his exegetical book on the Malay-Muslim community in Indonesia and Malaysia. The use of al-Islahi al-Ijtimāci methodology in the Tafsir al-Ma’rifah has succeeded in attracting the Malay-Muslim community in Indonesia and Malaysia to use the Tafsir al-Ma'rifah as a guide in their lives. The study adopted a qualitative research methodology using the content analysis method of the exegetical book. This study also used an interview method with the author. The results found that the Tafsir al-Ma'rifah is currently studying new problems at the present time by using the Malay language, which is easy to understand. The exegetical book also emphasizes the aspects of Islamic society, morals, and social life. The Tafsir al-Ma’rifah is a tafsir bi al-Ra'y (opinion-oriented interpretation), which uses the interpretation method ofTahlili al-Mawdu’i with the approach of al-Islahi al-Ijtimāci (social reform). The implication of this study is to introduce a Muslim scholar who can be a reference for researchers, scholars and the Malay-Muslim community in Indonesia and Malaysia.